Steady improvement of infection control services in six community hospitals in Makkah following annual audits during Hajj for four consecutive years - Alazraqi Tarik A; Alhazmi Mohammad A; Albarrak Ali M; Madani Tariq A; Althaqafi Abdulahakeem O; Ishaq Abdulrahman H (BMC Infectious Diseases, 2006)
Abstract Background the objective of this study was to evaluate the impact of annual review of the infection control practice in all Ministry of Health hospitals in the holy city of Makkah, Saudi Arabia, during the Hajj period of four lunar Islamic years, 1423 to 1426 corresponding to 2003 to 2006. Methods audit of infection control service was conducted annually over a 10-day period in six community hospitals with bed capacities ranging from 140 to 557 beds. Data were collected on standardized checklists on various infection control service items during surprise visits to the medical, pediatric, surgical, and critical care units, and the kitchens. Percentage scores were calculated for audited items. The results of the audit for hospitals were confidentially sent to them within four weeks after the end of Hajj. Results deficiencies observed in the first audit included lack of infection control committees, infection control units, infection control educational activities, and surveillance system and shortage of staff. These deficiencies were resolved in the subsequent audits. The average (range) scores of hospitals in 11 infection control items increased from 43% (20–67%) in the first audit to 78% (61–93%) in the fourth audit. Conclusion regular hospital infection control audits lead to significant improvement of infection control practice. There is a need to build a rigorous infection control audit into hospitals' ongoing monitoring and reporting to the Ministry of Health and to provide these hospitals with feed back on such audits to continuously strengthen the safety standards for patients, visitors, and employees.